(3CKQ GdeSGYOGJ GdEfeGFjI GdQSejI Ydi Gdfeh GdGbJUGOi ai djHjQjG efP YGe (B2003/ s - (3Cjef UdGM GdOjf EHQGgjes; (3SeGM SjO CMeO GdeQSi (B: s; (3eQhI YGOd GdMSfjf (B: s ((3GdbGgQI (B: s (3Cjef UdGM GdOjf EHQGgje (B: s, 2020)
(3gOaJ gPg GdOQGSI Edi JMdjd JWhQ bjeI GdeSGYOGJ GdEfeGFjI GdQSejI GdebOeI Edi djHjQjG(B: (3h Jbjje OhQ GdeSGYOGJ GdEfeGFjI GdQSejI ai Gdfeh GdGbJUGOi h JMdjd GdaQU h GdJMOjGJ GdJi JhGLg JMbjb GdGSJaGOI ef GdeSGYOGJ GdEfeGFjI GdQSejI ai djHjQjG(B: (3h bjGS CKQ GdeSGYOGJ GdEfeGFjI GdQSejI Ydi Gdfeh GdGbJUGOi(B. (3h bO bSeJ GdOQGSI Edi ebOeI h eHMK JegjOi h KdGKI aUhd h NGJeI(B: (3aGSJYQV GdeHMK GdJegjOi GdEWGQ GdfXQi ddeSGYOGJ GdEfeGFjI GdQSejI h JCKjQgG Ydi Gdfeh GdGbJUGOi(B: (3Ke JfGhd GdaUd GdChd JWhQ bjeI GdeSGYOGJ GdEfeGFjI GdQSejI ddjHjQjG h eUGOQgG h JhRjYgG Ydi GdbWGYGJ(B: (3h GSJYQV GdaUd GdKGfi eUahaI GdJMdjd GdQHGYi ddeSGYOGJ GdEfeGFjI GdQSejI GdebOeI Edi djHjQjG(B: (3Ke JfGhd GdaUd GdKGdK bjGS CKQ GdeSGYOGJ GdEfeGFjI Ydi Gdfeh GdGbJUGOi ai djHjQjG(B: (3Ke CNjQkG JfGhd GdeHMK GdNJGei fJGFL GdOQGSI h QDjI eSJbHdjI(B. (3h JeKdJ Cge GdfJGFL ajeG jdi(B: (3JNJda fJGFL GdCOHjGJ GdJi JfGhdJ CKQ GdeSGYOGJ GdEfeGFjI GdQSejI Ydi Gdfeh GdGbJUGOi dCOHjGJ hLOJ YdGbI WQOjI h GNQi hLOJ YdGbI YcSjI h GNQi hLOJ YdGbI HgG fbWI GfbdGH(B: (3aGYJeOJ djHjQG Ydi GdeSGYOGJ GdEfeGFjI h GNP GdGYJeGO YdjgG jROGO JOQjLjG(B: (3HGdQZe ef Cf JGQjN djHjQjG jfHC HGdGYJeGO Ydi GdPGJ h dcf GdMQH GdCgdjI GVYaJ GdGbJUGO h GHWCJ hJjQI Gdfeh(B: (3h dcf dOi djHjQG GdcKjQ ef GdaQU cGdGTJQGc ai eTGQjY GdHfjI GdJMJjI eY GdOhd GdeLGhQI(B: (3h RjGOI GdGgJeGe HGdZGHGJ GddjHjQjI(B. (3JHjf Cf GdeTGQcI ai Gdbhi GdYGedI dgG CKQkG EjLGHjG Ydi GdfGJL GdeMdi GdELeGdi Ydi YcS CKQ UGai GdeSGYOGJ GdEfeGFjI GdQSejI GdJi XgQ dgG JCKjQ SdHj Ydi GdfGJL GdeMdi GdELeGdis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdCaQjbjI GdYdjG (B- (3bSe GdfXe GdEbJUGOjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGbJUGO GddjHjQis; (3GdeSGYOGJ GdEfeGFjI GdQSejIs; (3Gdfeh GdGbJUGOis